Implementation of an all-ages mandatory helmet policy for ice skating. Issue 6 (13th February 2015) - Thibault-Halman, Ginette; Fenerty, Lynne; Wheadon-Hore, Kathie; Walling, Simon; Cusimano, Michael D; Clarke, David B
Abstract : Ice skaters sustain a significant number of head injuries each winter. We are the first to implement an all-ages helmet policy at a university-based Canadian arena. We report our experience from a cross-sectional observational study as well as the policy's consequences on helmet use and skating participation. Educational programming was provided prior to policy implementation. Observations of helmet use, falls and skater demographics were conducted prior to education/implementation and after policy implementation. The number of skaters observed was essentially unchanged by the policy; 361 skaters were observed pre-implementation, while 358 were observed post-implementation during the same number of observation-hours. Pre-implementation, helmet use ranged from 97% among children under 12 to 10% among adults; post-implementation use in all skaters was 99%. Falls were observed among all age groups, with preponderance among those aged 4–12. An all-ages helmet policy was successful both in achieving helmet use among all skaters and in maintaining participation rates.